THE CASE OF FALSE NEGATIVE RESULT OF HELIK-TEST OF PATIENT WITH CHRONIC NON - ATROPHIC GASTRITIS WITH INTRACELLULAR "DEPOT" HELICOBACTER PYLORI INFECTION - Avramenko, A.A. (World of Medicine and Biology, 2018)
The case of false negative result of HELIK test of 39-year old ill woman who has chronic non-atrophic gastritis was analyzed. In history, it was found that the current aggravation have arisen on the background of family stress, which lasted for 4 months. According to Order № 271 from 13.06.2005 of Ministry of HealthCare of Ukraine a patient took comprehensive examination (N 6459, 26.05.17), which included step-by-step рН-metry based on VN Chernobrovyi methods, esophagogastroduodenoscopy (EGDS) based on general techniques, helicobacter infection test (НР) (urease test and microscoping of stained smears with the determination of intracellular "Depot" HP on comparative characteristic) and histological investigations of the gastric stump mucous, biopsy material was taken from 4 topographical zones of the stomach (medial third part of antrum and body of the stomach through large and small curvature). Also further the breathing test was held to the patient (HELIK- test) to determine the level of HP infection using a generally accepted method and determination of the level of natural killers (CD-16) in the blood for the detection of intracellular "Depot" Helicobacter pylori infection. When conducting a comprehensive survey of the patient the presence of intracellular "Depot" Helicobacter pylori infection was found, confirmed by two different methods-comparative characteristic of the data of urease test and microscopy of smeared touch from 4 topographical zones of the stomach and on the level of natural killers (CD-16) in the blood. Thus, the intracellular "Depot" HP-infections are one of the factors that can lead to false- negative results of HELIK- test.
Keywords: chronic non-atrophic gastritis; intracellular "Depot" Helicobacter pylori infection; HELIK-test